Concurrent engineering in educational projects : case study Svartöberget - Jansson, Gustav; Johnsson, Helena (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2008)
Each year, Luleå University of Technology teach 40 civil engineering students and 45 architectural engineering students basic knowledge in the construction process through a simulated real-life situation. In the third year, the grand total of 85 students is brought together and taught their respective professional roles through acting as experts within 6 different fields in the realization of a residential area. Research in the last decades has identified concurrent engineering as a possible method for streamlining the design phase in the construction process. The student project was therefore planned with a concurrent engineering approach, where all student groups start their work at the same time. The pedagogy was to teach students a new approach to working in large projects, with the side effect of testing if concurrent engineering is feasible also in educational projects. Information is shared between groups through live documents on a project portal. Project coordination and communication is handled by 21 project leaders who meet regularly to exchange information between groups and detect missing information needed from other groups. Project planning is made through a method adopted from lean construction; Look Ahead Planning, which is part of the Last Planner method. IT-support is used to produce data and perform calculations but also as a tool for quality assurance across groups. All data is eventually summed up and presented in a virtual reality model of the new residential area. The VR model is gradually refined and the structure for delivering information into the model is drawn up by 6 appointed IT coordinators Godkänd; 2008; 20080825 (gusjan) Industriell byggprojektering